Oxytocin - Hernández Vargas, Melissa (2026)
Oxytocin is a contemporary tragedy based on real testimonies from Costa Rican women who have experienced obstetric violence. It emerged as an interdisciplinary artistic investigation and creation that seeks to highlight a form of systematic violence that is often normalized but leaves deep scars on the bodies and psyches of those who experience it. The project combines elements of theater, dance, visual arts, and social studies to denounce this violence from an intimate, poetic, and collective perspective.